Spatial Characterization of NDVI-Based Vegetation Density in Smallholder Coffee Plantation on Mount Kawi’s Southern Slopes - Dinna Hadi Sholikah; Nabilla Putry Maharani; Ramadhani Mahendra Kusuma; Dewi Shasa Bella; Yoga Gregorius Sembiring; Fitri Wijayanti; Soemarno Soemarno (Journal of Applied Agricultural Science and Technology, 2025)
Indonesia’s coffee cultivation covers 1.25 million hectares, predominantly managed by smallholders (98.14%). Malang Regency, a key production area in East Java, experienced a sharp yield decline from 29,728 tonnes (2021) to 14,151 tonnes (2022). This study investigates smallholder plantations in the Kletek sub-watershed, emphasising the role of shade vegetation in coffee growth. Shade density critically influences productivity and ecological resilience. To support sustainable management, vegetation cover is assessed via remote sensing using the Normalised Difference Vegetation Index (NDVI), enabling spatial analysis of canopy structure. This research aims to analyse the types of coffee shade trees on smallholder coffee farms. NDVI is used to distinguish differences in land cover, including coffee shade. The study employed a land survey using the grid method with 30 observation points. Spatial analysis involves spectral transformation of Sentinel-2A Harmonised imagery, while statistical analysis uses correlation tests. Smallholder coffee farms in the Kletek Sub-watershed feature shade plants such as lamtoro, mahogany, and banana trees. NDVI values across these plantations ranged from moderate (0.4–0.5) to very high (>0.6) vegetation density, showing a strong correlation with land cover conditions (r = 0.80). This confirms NDVI as an effective remote sensing tool for assessing shade vegetation, significantly influencing coffee productivity and ecological resilience. The findings support NDVI-based monitoring for precision agriculture and adaptive management, with scalable applications in sustainable land-use planning, agroforestry optimisation, and climate-resilient coffee cultivation in regions such as Malang Regency, where production has declined.